Answer:
The value of the expression 2*-2-(3- -2) is -9.
Step-by-step explanation:
2 x (-2)- (3- -2)
=2 x (-2)- (3+2)
=2 x (-2) -5
= -4-5
=<u><em>-9</em></u>
Hope this Helps!!!
Please consider this as brainliest, thanks!!!
It’s 5h because you aren’t adding homework, subtracting homework or dividing homework
Answer:
(_11)×15 please help help me me my question solve please
Answer:
Step-by-step explanation:
1. Use this to find the average rate of change
2. Average rate of change =
3. and (To find these you will need to look at the points on the graph. So the points (8,-4) and (6,-10))
4. Replace -4 to f(8) and -10 to f(6)
5. So it will look like
6. Solve
There's 4oz left
75%=3/4
so 3/4 of 16oz (one pint) is 4.